Gymnema sylvestre for Diabetes: From Traditional Herb to Future’s Therapeutic - Tiwari, Pragya; Ahmad, Khurshid; Hassan Baig, Mohammad (Current Pharmaceutical Design, 2017)
Diabetes has increased at an unprecedented rate and is fast emerging as a global threat worldwide. The focus on pharmacological studies pertaining to diabetes has seen a remarkable shift from conventional medicines to therapeutics employing bioactive phytomolecules from natural sources. The prospective effectiveness of natural products together with their low cost and minimal side effects has revolutionized the entire concept of drug discovery and management programs. One such beneficial herb is Gymnema sylvestre, possessing remarkable hypoglycemic properties and forms the platform of diabetes therapeutics in the traditional system of medication. The present article discusses the significance of G. sylvestre in diabetes management, the herbal-formulations from the herb together with its standardization and clinical trials on animal models, and why Peroxisome Proliferator Activated Receptor gamma (PPARγ) may serve as a prospective molecular target for Gymnemic acid analogs. Such studies would define the molecular basis of bioactive molecules which would aid in the development of natural product based therapeutics in the treatment of diabetes.
Keywords: diabetes